Preservation of total phenolic content (TPC) in cucumber juice concentrate using non-thermal Progressive Freeze Concentration: Quantitative design characteristics and process optimization - Mohd Rosli, N.N.H. (Elsevier Ltd, 2022)
Progressive freeze concentration (PFC) was used to concentrate cucumber juice to preserve total phenolic content (TPC) in this work as a non-thermal process. Since the productivity of PFC is always an issue, this work aimed to carefully fabricate an ice crystallizer with quantified design characteristics and optimized for an effective cucumber juice concentration process. A new device called Multiple Probe Cryo-Concentrator (MPCC) was designed, and to quantitatively identify the PFC design characteristics, the improvement in ice crystallization surface area coupled with appropriate apparatus shape factor and mixing power consumption were first calculated. From these analyses, it was observed that the improved surface area of the MPCC has given 35.44 improvement in terms of productivity and excellent fluid movement provided by the shape factor and mixing power consumption. With the aid of central composite design (CCD), the PFC operating parameters were then optimized to obtain the most effective values of effective partition constant, K-value (0.381) and TPC increment (30.13) using multi-response optimization. The achieved optimum conditions included operation time of 35 min, initial concentration of 6 mg/ml, coolant temperature of â10.7 Â°C and stirrer speed of 400 rpm. From the regression modelling analysis and graphical plots, it was found that the stirrer speed has the most significant impact towards solute concentration in cucumber juice. In overall, it is evident that the design characteristics of the apparatus play an important role in giving a better PFC performance. Optimizing the PFC system for better efficiency can successfully maximize the nutritional properties, simultaneously indicating its high practicality in other fruit or vegetable juice concentration. Â© Elsevier Ltd